Adapalene inhibits the growth of triple-negative breast cancer cells by S-phase arrest and potentiates the antitumor efficacy of GDC-0941 - Mehraj, Umar; Wani, Nissar Ahmad; Hamid, Abid; Alkhanani, Mustfa; Almilaibary, Abdullah; Mir, Manzoor Ahmad (Frontiers in Pharmacology, 2022)
Although advances in diagnostics and therapeutics have prolonged the survival of triple-negative breast cancer (TNBC) patients, metastasis, therapeutic resistance, and lack of targeted therapies remain the foremost hurdle in the effective management of TNBC. Thus, evaluation of new therapeutic agents and their efficacy in combination therapy is urgently needed. The 3rd generation retinoid adapalene (ADA) has potent anti-tumor activity, and using ADA in combination with existing therapeutic regimens may improve the effectiveness and minimize the toxicities and drug resistance. The current study aimed to assess the anticancer efficacy of adapalene as a combination regimen with PI3K inhibitor (GDC-0941) in TNBC in vitro models. Chou-Talalay's technique evaluated the pharmacodynamic interactions (synergism, antagonism, or additivity) of binary drug combinations. Flow cytometry, western blotting, and in silico studies were used to analyze the mechanism of GDC-ADA synergistic interactions in TNBC cells. The combination of GDC and ADA demonstrated a synergistic effect in inhibiting proliferation, migration, and colony formation of tumor cells. Accumulation of reactive oxygen species upon co-treatment with GDC and ADA promoted apoptosis and enhanced sensitivity to GDC in TNBC cells. The findings indicate that ADA is a promising therapeutic agent in treating advanced BC tumors and enhances sensitivity to GDC in inhibiting tumor growth in TNBC models while reducing therapeutic resistance.